An integrated model on online tax adoption in Malaysia - Hussein, Ramlah; Mohamed, Norshidah; Ahlan, Abdul Rahman; Mahmud, Murni; Aditiawarman, Umar (Brunel University, 2010)

(untitled)
As one of the MSC Malaysia Flagship Applications, Online Tax System or e-Filing has gained its popularity since it was launched in 2006. But the obstacles remain concern taxpayers who are really anxious about the technology, lacking of technical skills, or do not trust of any online transaction. This has led to the investigation of the factors that might contribute to the taxpayers’ adoption of the online tax or e-Filing system. To fulfill this aim, a model of online tax adoption was developed by integrating the Technology Acceptance Model (TAM) theory, Diffusion and Innovation (DOI) theory, Perceived Characteristics of Innovating (PCI) and other relevant factors including social influence, web-based service quality, trust of the internet, trust of the government political self efficacy, and perceived risk. Thirteen main hypotheses were developed and tested. The results demonstrate that trust of the government and web-based service quality are found to be a significant factors influencing citizens’ intention to use e-Filing. Key implications for theory and practice are also discussed.